2020
DOI: 10.18103/mra.v8i7.2169
|View full text |Cite
|
Sign up to set email alerts
|

"Desert Chemotypes": The Potential of Desert Plants-Derived Metabolome to Become a Sustainable Resource for Drug Leads

Abstract: Plants secondary metabolites that are essential for plant survival in its environment are a useful resource for drug discovery in the area of combination therapy. Desert plants, in particular, have a lot to offer; they experience stress conditions and activation/repression of pathways that lead to biosynthesis of unique compounds. The current knowledge on the effectiveness of combination therapy as compared to single treatment support the use of active plant-derived extracts or fractions composed of several me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Studies have shown that soil-and plant-associated microbiomes could function as biofertilizers and biocontrol agents to enhance soil hydraulic properties 11 , fertility, plant stress tolerance, and productivity [12][13][14][15] . Studies on desert metabolites focused on plant-and endophytes-derived metabolites, which are important for environmental adaptation and drug discovery 16,17 . However, fewer studies focused on the dynamics and functional role of soil microbiome during long-term desert ecosystem restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that soil-and plant-associated microbiomes could function as biofertilizers and biocontrol agents to enhance soil hydraulic properties 11 , fertility, plant stress tolerance, and productivity [12][13][14][15] . Studies on desert metabolites focused on plant-and endophytes-derived metabolites, which are important for environmental adaptation and drug discovery 16,17 . However, fewer studies focused on the dynamics and functional role of soil microbiome during long-term desert ecosystem restoration.…”
Section: Introductionmentioning
confidence: 99%